We define:

series $\sum_{n=1}^{\infty} a_n$

$s_n=\sum_{k=1}^{n} a_k, n\in \mathbb{N}.$

$\sigma_n=\frac{1}{n}\sum_{k=1}^n s_k$

$s=\lim_{n\to \infty} s_n$

Proposition: If sequence $(s_n)_n$ converges and if $s=\lim_{n\to \infty} s_n$ then sequence $(\sigma_n)_n$ also converges and $s=\lim_{n\to \infty} \sigma_n$.

Proof: Let $s=\lim_{n\to \infty} s_n$ and $\epsilon \gt0$. Let $\epsilon_n=s_n-s,n\in \mathbb{N}$.There exists $m\in \mathbb{N}$ so that $\forall n\in \mathbb{N}, (n\gt m) \Rightarrow (|\epsilon_n \lt \frac{\epsilon}{3}|)$. Now for $n \gt m+1$ we have $$\sigma_n=\frac{s_1+...+s_{m+1}}{n}+\frac{s_{m+2}+...+s_n}{n} =$$ $$\frac{s_1+...+s_{m+1}}{n}+\frac{n-m-1}{n}s+\frac{\epsilon_{m+2}+...+\epsilon_n}{n}$$

From that we have (and I don't understand why)$$|\sigma_n-s|\lt \frac{|s_1+...+s_n|}{n}+\frac{m+1}{n}|s|+\frac{n-m-1}{n}\frac{\epsilon}{3}$$

Lets take $n_{\epsilon} \gt m+1$ so that $\frac{|s_1+...+s_n|}{n_{\epsilon}}\lt \frac{\epsilon}{3}$ and $\frac{(m+1)|s|}{n_{\epsilon}} \lt \frac{\epsilon}{3}$.

Now, $\forall n\in \mathbb{N}, (n \gt n_{\epsilon}) \Rightarrow |\sigma_n-s|\lt \epsilon$


If someone could explain that transition, I'd be happy.


Subtract $s$ from $\sigma_n$, take absolute values, and apply the triangle inequality:

$$\begin{align*} \left|\sigma_n-s\right|&=\left|\frac{s_1+\ldots+s_{m+1}}n-\frac{m+1}ns+\frac{\epsilon_{m+2}+\ldots+\epsilon_n}n\right|\\ &\le\frac{|s_1+\ldots+s_{m+1}|}n+\frac{m+1}n|s|+\frac{|\epsilon_{m+2}|+\ldots+|\epsilon_n|}n\\ &<\frac{|s_1+\ldots+s_{m+1}|}n+\frac{m+1}n|s|+\frac{n-m-1}n\cdot\frac{\epsilon}3\;. \end{align*}$$

The final step uses the fact that each $|\epsilon_k|<\frac{\epsilon}3$, and there are $n-m-1$ of these $\epsilon_k$ terms in the numerator.


First, note that $$ \left|\frac{n-m-1}{n}s-s\right|=\left|\frac{n-m-1}{n}s-\frac{n}{n}s\right|=\left|\frac{-m-1}{n}s\right|=\frac{m+1}{n}\left|s\right|. $$ Next, since $m$ is chosen so that $|\epsilon_{n}|<\epsilon/3$ for all $n>m$, $$ \left|\frac{\epsilon_{m+2}+\cdots+\epsilon_{n}}{n}\right| \leq \frac{|\epsilon_{m+2}|+\cdots+|\epsilon_{n}|}{n} <\frac{\overbrace{\epsilon/3+\cdots+\epsilon/3}^{n-m-1\text{ terms}}}{n}=\frac{n-m-1}{n}\frac{\epsilon}{3}. $$

  • $\begingroup$ If you found any of the answers helpful, please consider upvoting or accepting; this is a good policy to follow on all questions you ask. (Personally, I think Brian's answer is nicer than mine, so consider accepting that one ^_^) $\endgroup$ – parsiad Sep 4 '16 at 17:19
  • $\begingroup$ I think that it’s a tossup! $\endgroup$ – Brian M. Scott Sep 4 '16 at 17:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.